Analysis of alternatives for the use or final disposal of the sludge generated at the Paipa (Boyacá) mini-wastewater treatment plant - Cepeda Arias, Édisson Ramiro; Montañez Pérez, José Salvador (Universidad Pedagógica y Tecnológica de Colombia, 2009)
The analysis of the physical, chemical and microbiological characteristics of the sludge produced under a biological domestic wastewater treatment system is presented, specifically of activated sludge with extended aeration for a plant that treats a flow of 103 m3 / h. The sludge generated in the Paipa Wastewater Treatment Plant was classified according to the concentrations of heavy metals and pathogens present, in accordance with current international regulations, and the different alternatives for use or final disposal were analyzed, supported by Colombian preliminary regulations. and international standards, it also includes the analysis of the final disposal without any intention of recycling or recovery, such as the sanitary landfill and incineration, together with the evaluation of the different alternatives to propose the most viable solution from the point from an environmental, health, economic and social perspective.